Keabsahan Proses Pembuktian Perkara Pidana Dalam Persidangan Yang Bersifat Online - Tirza Gloria Latupeirissa; Deassy Jacomina Anthoneta Hehanussa; Julianus Edwin Latupeirissa (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: Writing with the title: "The Validity of the Process of Proving Criminal Cases in Online Trials", has a problem formulation whether the process of proving criminal cases carried out online is accepted according to the Criminal Procedure Code and how to prove criminal cases ideally.Purposes of the Research:  This writing is intended to analyze and explain the process of proving criminal cases in online courts and ideally proving criminal cases.Methods of the Research: This writing uses a normative juridical research method, the legal materials used are secondary legal materials obtained through library research on primary, secondary and tertiary legal materials. Legal materials are discussed with a statutory approach, a concept approach and a case approach.Results of the Research: That in principle the process of proving criminal cases conducted online can be accepted according to the Criminal Procedure Code as an effort to fill the legal vacuum in the case of "certain circumstances" which are determined as emergencies or other circumstances. Whereas a criminal case evidence is said to be ideal, both in direct/normal trial and electronic/online trial, if it has fulfilled the evidentiary parameters, namely: implementation of proof principles/theory; evidence; submission of evidence; burden of proof; power of proof; and minimal evidence.